2022
DOI: 10.1002/ijc.34295
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a risk‐adapted screening strategy for prostate cancer: First results of the PROBASE trial

Abstract: PROBASE is a population‐based, randomized trial of 46 495 German men recruited at age 45 to compare effects of risk‐adapted prostate cancer (PCa) screening starting either immediately at age 45, or at a deferred age of 50 years. Based on prostate‐specific antigen (PSA) levels, men are classified into risk groups with different screening intervals: low‐risk (<1.5 ng/ml, 5‐yearly screening), intermediate‐risk (1.5‐2.99 ng/ml, 2 yearly), and high risk (>3 ng/ml, recommendation for immediate biopsy). Over the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…35,36 According to the data presented in this article, patients are more willing to undergo biopsy when the indication is underlined with MRI results, which is an important factor in achieving better outcomes and a more equal distribution of health care resources. 5,[37][38][39] In modeling studies, MRI-based PCa screening is associated with an improvement in the benefit-harm profile, quality of life, costeffectiveness, and environmental effect of screening for PCa compared with standard PSA-based screening. [40][41][42][43][44] Accordingly, our results synthesizing high-quality prospective data suggested that MRI is effective at identifying individuals who are most likely to require further evaluation and biopsy, potentially reducing the burden on health care resources and sparing patients from having to undergo unnecessary invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 According to the data presented in this article, patients are more willing to undergo biopsy when the indication is underlined with MRI results, which is an important factor in achieving better outcomes and a more equal distribution of health care resources. 5,[37][38][39] In modeling studies, MRI-based PCa screening is associated with an improvement in the benefit-harm profile, quality of life, costeffectiveness, and environmental effect of screening for PCa compared with standard PSA-based screening. [40][41][42][43][44] Accordingly, our results synthesizing high-quality prospective data suggested that MRI is effective at identifying individuals who are most likely to require further evaluation and biopsy, potentially reducing the burden on health care resources and sparing patients from having to undergo unnecessary invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, avoiding biopsy and following up with patients with negative MRI results were shown to be a safe approach in screening . According to the data presented in this article, patients are more willing to undergo biopsy when the indication is underlined with MRI results, which is an important factor in achieving better outcomes and a more equal distribution of health care resources . In modeling studies, MRI-based PCa screening is associated with an improvement in the benefit-harm profile, quality of life, cost-effectiveness, and environmental effect of screening for PCa compared with standard PSA-based screening .…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have concluded that prostate cancer screening does not improve mortality [ 37 ]. Therefore, some studies recommend optimizing screening criteria to target high-risk populations, as well as increasing awareness and education on the risks and benefits of prostate cancer screening to make informed decisions [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Attendance to scheduled screening visits over the first 6 years varied from 70% to 79% across risk groups. 95 Other ongoing prostate cancer screening studies Many non-randomised, prospective prostate cancer screening studies are ongoing. Several evaluate screening of high-risk populations: The UK BARCODE-1 investigates a polygenic risk score for targeting a high-risk population.…”
Section: Probase (Germany)mentioning
confidence: 99%